Optimization of Design Mix Proportion for Saturated Water Absorption of High Performance Concrete - M. Akila; Chithra, S. (Asian Journal of Engineering and Applied Technology, 2018)
This study involves the optimization of design mix proportion for saturated water absorption of high performance concrete (HPC) by Taguchi Method. In the present investigation, saturated water absorption test on 25 HPC mixes specimens made with colloidal nano silica and copper slag as replacement of cement and fine aggregate respectively has been conducted at the age of 28 days and 90 days of water curing. The concrete mixes has been replaced by 1%, 1.5%, 2%, 2.5%, 3% of nano silica and copper slag of 10%, 20%, 30%, 40%, 50%. From Signal-to-Noise ratio, the optimal parametric combination for saturated water absorption has been obtained. The Analysis of Variance has been done on experimental data values. The percentage contribution of the factors towards saturated water absorption is identified. The nano silica contributes towards less water absorption in 28 days curing, while the Copper slag found to the major contributing factor for the cause after the 90 days tenure of water curing.